2018
DOI: 10.1038/s41467-017-02694-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics identifies redox switches for global translation modulation by mitochondrially produced reactive oxygen species

Abstract: The generation of reactive oxygen species (ROS) is inevitably linked to life. However, the precise role of ROS in signalling and specific targets is largely unknown. We perform a global proteomic analysis to delineate the yeast redoxome to a depth of more than 4,300 unique cysteine residues in over 2,200 proteins. Mapping of redox-active thiols in proteins exposed to exogenous or endogenous mitochondria-derived oxidative stress reveals ROS-sensitive sites in several components of the translation apparatus. Mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
202
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(227 citation statements)
references
References 68 publications
24
202
1
Order By: Relevance
“…The second band corresponded to the binding of PEG‐PCMal to three cysteine residues (C4, C53, and C55). The CPC motif of MIA40 was oxidized to a similar extent in COA7‐overexpressed and control samples although an overall level of oxidation was higher in isolated mitochondria than in total cells (Fig D, lanes 3 and 4, , lanes 1 and 2) which is consistent with partial oxidation of proteins during mitochondria isolation (Topf et al , ). Thus, we confirmed that COA7 overexpression did not affect the redox state of cysteine residues in the CPC motif, suggesting that both cysteine residues were equally available for importing MIA40 substrates, such as TIMM8A and COX19.…”
Section: Resultssupporting
confidence: 70%
“…The second band corresponded to the binding of PEG‐PCMal to three cysteine residues (C4, C53, and C55). The CPC motif of MIA40 was oxidized to a similar extent in COA7‐overexpressed and control samples although an overall level of oxidation was higher in isolated mitochondria than in total cells (Fig D, lanes 3 and 4, , lanes 1 and 2) which is consistent with partial oxidation of proteins during mitochondria isolation (Topf et al , ). Thus, we confirmed that COA7 overexpression did not affect the redox state of cysteine residues in the CPC motif, suggesting that both cysteine residues were equally available for importing MIA40 substrates, such as TIMM8A and COX19.…”
Section: Resultssupporting
confidence: 70%
“…For example, translation by the bacterial ribosome is inhibited by oxidation of the rRNA bases within the peptidyl transferase center (3). Reversible oxidation of cysteine residues in ribosome-associated proteins under conditions of increased ROS generation was proposed to attenuate translation (4). Oxidative damage to rRNA has been hypothesized to play a role in neurodegenerative disease (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The second study applied quantitative redox proteomics based on the OxICAT approach and identified 41 proteins that underwent substantial thiol modifications as a result of H 2 O 2 treatment. Using similar thiol labeling but different MS workflow, the third study identified 47 unique proteins with redox‐active thiols . Strikingly, there was very limited overlap between these datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Nrp1 also belongs to the group of Zn 2+ finger proteins, with a currently uncharacterized RNA binding function, also localizing to stress granules. From a functional point of view, the redox‐sensitivity of these proteins can play a critical role in the global attenuation of translation in response to oxidative stress . Further candidates for redox‐regulated conditional disorder include other Zn 2+ binding proteins, such as the DNA damage‐responsive transcriptional repressor Rph1, pre‐mRNA‐splicing factor Rds3, and DNA‐directed RNA polymerases I, II, and III subunit Rpabc4 (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation